Towards a plan for Kuils River - Lipman, E. N (School of Architecture, Planning and Geomatics, 2024)
[61-67 missing] A primary aim of the study is seen to lie in the establishment of criteria which could ultimately form the basis or a land-use "plan", or policy for Kuils River. It is therefore considered fundamental to establish, in the first instance; the role of Kuils River in the region. It, furthermore, becomes necessary to define the local physical environment. This would serve to establish qualitative features as well as constraints which could determine future planning decisions.